2022
DOI: 10.3389/fpsyg.2022.914528
|View full text |Cite|
|
Sign up to set email alerts
|

Does User Preference Matter? A Comparative Study on Influencing Factors of User Activity Between Government-Provided and Business-Provided Apps

Abstract: The competition between government-provided apps and business-provided apps for active users in China is becoming increasingly fierce. Apps with higher user activity will win this competition. To maintain active users, finding the user activity influencing factors is crucial. In this study, we selected a government-provided app—“Beijing One Card”- and a business-provided app—“Bus Code” (the Beijing area) -in the field of public transportation as the comparative research objects. Based on multiple regression an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 39 publications
(18 reference statements)
0
1
0
Order By: Relevance
“…Therefore, the second perspective suggests that public satisfaction significantly influences public favorability [27]. Guo [28] conducted a study comparing public favorability between governmental and commercial apps. The findings revealed that, in comparison to commercial apps, the public tends to prefer governmental apps.…”
Section: Theoretical Foundationmentioning
confidence: 99%
“…Therefore, the second perspective suggests that public satisfaction significantly influences public favorability [27]. Guo [28] conducted a study comparing public favorability between governmental and commercial apps. The findings revealed that, in comparison to commercial apps, the public tends to prefer governmental apps.…”
Section: Theoretical Foundationmentioning
confidence: 99%